Immune Dysregulation and Infectious Complications in MPN Patients Treated With JAK Inhibitors - Cattaneo, Daniele; Iurlo, Alessandra (Frontiers in Immunology, 2021)
BCR-ABL1-negative myeloproliferative neoplasms are burdened by a reduced life expectancy mostly due to an increased risk of thrombo-hemorrhagic events, fibrotic progression/leukemic evolution, and infectious complications. In these clonal myeloid malignancies JAK2V617F is the main driver mutation, leading to an aberrant activation of the Janus kinase-signal transducer and activator of transcription (JAK-STAT) signaling pathway. Therefore, its inhibition represents an attractive therapeutic strategy for these disorders. Several JAK inhibitors have entered clinical trials, including ruxolitinib, the first JAK1/2 inhibitor to become commercially available for the treatment of myelofibrosis and polycythemia vera. Due to interference with the JAK-STAT pathway, JAK inhibitors affect several components of the innate and adaptive immune systems such as dendritic cells, natural killer cells, T helper and regulatory T cells. Therefore, even though the clinical use of these drugs in MPN patients has led to a dramatic improvement of symptoms control, organ involvement and quality of life, JAK inhibitors-related loss of function in JAK-STAT signaling pathway can be a cause of different adverse events, including those related to a condition of immune suppression or deficiency. This review article will provide a comprehensive overview of the current knowledge on JAK inhibitors’ effects on immune cells as well as their clinical consequences particularly with regards to infectious complications.